2020
DOI: 10.1177/1087054720969977
|View full text |Cite
|
Sign up to set email alerts
|

ADHD May Associate With Reduced Tolerance to Acute Subconcussive Head Impacts: A Pilot Case-Control Intervention Study

Abstract: Objective: To test our hypothesis that individuals with ADHD would exhibit reduced resiliency to subconcussive head impacts induced by ten soccer headings. Method: We conducted a case-control intervention study in 51 adults (20.6 ± 1.7 years old). Cognitive assessment, using ImPACT, and plasma levels of neurofilament-light (NF-L), Tau, glial-fibrillary-acidic protein (GFAP), and ubiquitin-C-terminal hydrolase-L1 (UCH-L1) were measured. Results: Ten controlled soccer headings demonstrated ADHD-specific transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Because cognitive testing detects changes in memory and attention, the effects of RHI may have been obscured in athletes with concomitant attentional deficits. This was highlighted in a recent study that ADHD may induce reduced cognitive resiliency to RHIs such that soccer players with ADHD showed significant decline in memory functions after 10 short-term soccer headings, whereas soccer players without ADHD showed no remarkable change 37. In addition, cognitive studies that examined younger children were more likely to report no effect of RHIs on cognition, possibly due to children being outliers in age and cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Because cognitive testing detects changes in memory and attention, the effects of RHI may have been obscured in athletes with concomitant attentional deficits. This was highlighted in a recent study that ADHD may induce reduced cognitive resiliency to RHIs such that soccer players with ADHD showed significant decline in memory functions after 10 short-term soccer headings, whereas soccer players without ADHD showed no remarkable change 37. In addition, cognitive studies that examined younger children were more likely to report no effect of RHIs on cognition, possibly due to children being outliers in age and cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 34 included articles, the vast majority relied on self-reported ADHD/LD status using ImPACT’s demographic history section or study-specific history questionnaires. Only three studies directly evaluated study participants’ neurodevelopmental history using either semistructured interview (i.e., Kiddie Schedule for Affective Disorders and Schizophrenia; Biederman et al, 2015; Iaccarino et al, 2018) or documentation of previous evaluation by a health care provider (i.e., neuropsychologist, psychiatrist, neurologist) and additional administration of an ADHD symptom checklist (Nowak et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Of these articles, 13 directly compared mean differences in performance on ImPACT Composite scores between ADHD and/or LD groups and healthy athletes (Biederman et al, 2015; Brooks et al, 2016; Cottle et al, 2017; Covassin et al, 2013; Elbin et al, 2013; Iaccarino et al, 2018; Kaye et al, 2019; Maietta, Kuwabara, et al, 2021; L. Manderino & Gunstad, 2018; Mautner et al, 2015; Peltonen et al, 2019; Salinas et al, 2016; Zuckerman et al, 2013), whereas five articles investigated additional aspects of baseline performance, for example, predictors of low performance (Brett, Solomon, et al, 2018; Brooks et al, 2018; Cook et al, 2017; Gardner et al, 2017; Houck et al, 2019) and one additional article utilized an experimental paradigm to assess ADHD effects on cognition post 10 soccer headings (Nowak et al, 2022). Table 2 provides details of these articles’ findings with a visual summary of the findings presented in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While pyschostimulants methylphenidate (MPH) or amphetamines remain the first line of ADHD treatment [8][9][10], there is a growing appreciation for the beneficial role of nonpharmacological therapies. These include the use of physical activities such as exercise and sports [11][12][13]. A recent meta-analysis of 30 studies showed that moderate to intense aerobic exercise can be effective in the management of the cognitive and behavioral symptoms of ADHD [14].…”
Section: Introductionmentioning
confidence: 99%